Bolalar ongida madaniyatning oʻrni - Berkinov Oybek Toxir o’g’li, Abdugʻopurova Kimyoxon Adxam qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
An important factor that forms spirituality in young people is the education system. It is necessary to look at knowledge and education as the main condition of human perfection and development of the nation. For this reason, it is stipulated in our Constitution that the issue of school and youth education is under the control of the state. Correct definition of the role of culture in the formation and development of human society is of great theoretical and practical importance.